PENGARUH INTELLIGENCE QUOTIENT (IQ) DAN EMOTIONAL SPIRITUAL QUOTIENT (ESQ) TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMA (STUDI KORELASI SISWA SMA SE-KOTA SERANG) - Ayu Lestari; Cecep Anwar Hadi Firdos Santosa; Ria Sudiana (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This study aims to determine the effect of Intelligence Quotient (IQ) and Emotional Spiritual Quotient (ESQ) on mathematics learning outcomes of high school students in Serang City in class XI, totaling 173 students. Methods are in use is survey method with approach quantitative.  Instruments that are used include questionnaire ESQ, portfolio results test IQ students and the value of UAS even the eyes of subjects mathematics compulsory students when class X. Technical analysis of the data that is used is analysis of statistical descriptive and statistical inferential includes testing prerequisites in the form of test for normality and test linearity, test the assumption of the classical form of the test multicollinearity and test heteroscedaticity, then do test the hypothesis in the form of test analysis of regression simple and test analysis regression multiple . The results of this study indicate that there is a positive influence between the Intelligence Quotient (IQ) and the mathematics learning outcomes of high school students, there is a positive influence between the Emotional Spiritual Quotient (ESQ) and the mathematics learning outcomes of high school students, and there is a positive influence between the Intelligence Quotient (IQ), Emotional Spiritual Quotient (ESQ) and mathematics learning outcomes of high school students.